A Novel Pathogenic Variant of the CFTR Gene in a Patient with Cystic Fibrosis Phenotype—c.4096A > T - Arslan, Ahmet Burak; Zamani, Ayşe Gül; Pekcan, Sevgi; Yıldırım, Mahmut Selman (Journal of Pediatric Genetics, 2020)
Cystic fibrosis is a chronic multisystemic disease originating from functional alterations in CFTR (cystic fibrosis transmembrane conductance regulator) protein. To date, more than 300 pathogenic variants have been described in the literature. However, the diagnosis of CF, which was thought to become easier after the CFTR gene was identified, became more complicated due to the enormous amount of variations. In this study, we present a patient whose clinical findings were consistent with cystic fibrosis (CF) and showed a homozygous missense change that is not previously reported in the CFTR gene as pathogenic. In the next-generation sequencing analysis, homozygous c.4096A > T single-nucleotide exchange (I1366F [p.Ile1366Phe], missense) was shown in both alleles of the patient' CFTR gene. According to our database analysis, this variant has not yet been previously reported (VarSome, ClinVar, MutationTaster, Ensembl, dbSNP, PubMed). We do consider the change as pathogenic since the patient's findings were compatible with CF and the data analysis was in favor of pathogenicity. The most recent consensus report published in 2017 emphasized the importance of CFTR gene analysis, and this study emphasizes the difficulties of associating CFTR gene variations with a clinical picture and constitutes a new data on the genotype–phenotype correlation of CFTR variants. Also, considering the frequency of CF (according to World Health Organization data, every 1 out of 2,000–3,000 infants is born with CF in European Union countries and every 1 out of 3,500 in the United States) as well as the increasing rate of molecular studies performed on CF patients worldwide, reporting novel variation has an additional value.
Keywords: CFTR (cystic fibrosis transmembrane conductance regulator); novel; pathogenic variant; cystic fibrosis; next-generation sequencing